2018
DOI: 10.3389/fimmu.2018.00047
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibodies Induced by Gene-Based Hydrodynamic Injection Have a Therapeutic Effect in Lethal Influenza Infection

Abstract: The influenza virus causes annual epidemics and occasional pandemics and is thus a major public health problem. Development of vaccines and antiviral drugs is essential for controlling influenza virus infection. We previously demonstrated the use of vectored immune-prophylaxis against influenza virus infection. We generated a plasmid encoding neutralizing IgG monoclonal antibodies (mAbs) against A/PR/8/34 influenza virus (IAV) hemagglutinin (HA). We then performed electroporation of the plasmid encoding neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 65 publications
4
33
1
Order By: Relevance
“…In our previous report (31) and others (29,30), HD can also induce gene expression in other organs, including the spleen. Clark and colleagues mainly focused on splenic B cells and demonstrated that in B cell-activating factor receptor (BAFFR)-deficient mice, which lack mature B cells but produce T1 B cells (57), anti-RP105 mAb bound to the antigen could also induce the production of antigen-specific antibodies (4,18).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…In our previous report (31) and others (29,30), HD can also induce gene expression in other organs, including the spleen. Clark and colleagues mainly focused on splenic B cells and demonstrated that in B cell-activating factor receptor (BAFFR)-deficient mice, which lack mature B cells but produce T1 B cells (57), anti-RP105 mAb bound to the antigen could also induce the production of antigen-specific antibodies (4,18).…”
Section: Discussionmentioning
confidence: 72%
“…Allophycocyanin (APC)-conjugated goat anti-mouse IgG(H+L) (Southern Biotech), FITC-conjugated rat anti-mouse IgG1 (RMG1-1; BioLegend, San Diego, CA, USA), APC-conjugated rat anti-mouse IgD (11-26c.2a), PerCP-conjugated or PE-conjugated rat anti-mouse B220 (RA3-6B2), biotinylated rat anti-mouse CD86 (GL-1), APC-conjugated streptavidin, PE-conjugated streptavidin, and FITC-conjugated rat anti-mouse IgM (eB121-15F9; eBioscience, San Diego, CA, USA) were purchased. We prepared biotinylated mouse anti-HA IgG1 ( 31 ), parental anti-RP105 mAb (rat), mouse anti-MD-1 (JR7G1) ( 35 ), and unconjugated anti-HA IgD ( 31 ). The parental anti-RP105 mAb (rat) was obtained from the supernatant of the hybridoma ( 14 ) ( Figures 1B, C ) or purified from ascites fluid, which was obtained from pristane (Funakoshi, Tokyo, Japan)-primed nude mice that were intraperitoneally inoculated with the hybridoma ( 36 , 37 ) using the caprylic acid (Wako, Tokyo, Japan)-ammonium sulfate (Katayama Kagaku, Osaka, Japan) precipitation method ( 38 ) ( Figures 2A, B ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After 14 days, their serum was obtained. The next day, the mice were intranasally infected with a lethal dose of A/PR8 virus (1,000 PFU/50 µl, 40 LD 50 ), as previously described (31,43). Three days post-infection, bronchoalveolar lavage specimens were obtained, and viral titers were determined by a plaque assay.…”
Section: Dna Immunization and Virus Challengementioning
confidence: 99%